ANALYSIS OF LAND DISPUTES BETWEEN THE COMMUNITY AND ASSEGAF FAMILIES IN KENTEN VILLAGE, TALANG KELAPA DISTRICT, BANYUASIN REGENCY - Gantama NJ, Razin; Juainah, Norma; Anisyah, Siti (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
In some areas, such as Kenten Village, Talang Kelapa District, and Banyuasin Regency, land conflicts are a frequent problem. This research aims to examine various land disputes that occurred between the Assegaf family and the community, as well as efforts to resolve them. This research combines a qualitative approach with a descriptive strategy. Data collection techniques include documentation, interviews, and observations. The study found that land disputes occurred due to claims of dual ownership of the same land between the community and the Assegaf family, which was exacerbated by weak land administration and overlapping certificates. Efforts to resolve disputes have been carried out through mediation, both by the village government and related agencies, but until now they have not produced a complete solution. This study concludes that land dispute resolution requires a firmer approach from the government, including strengthening regulations and transparency in the issuance of land certificates. It is hoped that the findings of this study can add references to the peaceful and fair resolution of agrarian conflicts.